Pengaruh Lingkungan Internal Dan Strategi Inovasi Terhadap Kinerja Perusahaan (Studi Pada PT.Glostar Indonesia 1 Cikembar) - Risma Melati; Erry Sunarya; Dicky Jhoansyah (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Glostar Indonesia 1 Cikembar is a company engaged in shoes manufacturing. The problems identified at PT. Glostar Indonesia was unachieved target of production that had been set by the company. The problem was predicted to be caused by machine breakdowns during production activities and the lack of awareness as well as sense of responsibility of employees towards the company's goals. The research was aimed at determining the amount of the influence of internal environment towards firm performance as well as finding out the amount of the influence of innovation strategy towards firm performance at PT. Glostar Indonesia 1 Cikembar.Objects of the research were Internal Environment (X1), Innovation Strategy (X2) and Firm Perfromance (Y). The method applied in the research was quantitative with descriptive and associative approach. The technique of sampling used in the research was saturated sampling method (census). Samples taken in the research were amounted to 35 namely the management level of PT. Glostar Indonesia 1 Cikembar consisted of managers and supervisors. The techniques of analzying data used were multiple linear regression analysis including determination coefficient test, multiple linear coefficients, simultaneous (F test) and partial (T test) tests. Based on the results of the research obtained, there is a positive and significant influence from internal environment variable towards firm performance amounted to 0.751. There is also a positive and significant influence from innovation strategy towards firm performance amounted to 0.956. Subsequently, there is a positive and significant influence from both internal environment and innovation strategy in improving firm performance amounted to 0.984 or namely 96.8%; meanwhile, the rest of 0.32 or namely 32% is influence by other factors out of this research. From the above results it can be interpreted that there is a positive and significant influence from internal environment variable and innovation strategy variable in improving firm performance. Keywords : Internal Environment, Innovation Strategy, Firm Performance